Inter-ethnic redistribution and human investments - Leonid V. Azarnert (Bar-Ilan University, Department of Economics, 2009)
This article analyzes income redistribution in the inter-ethnic context. The model shows that redistribution in favor of less prosperous ethnic minorities raises fertility among the unskilled minority recipients, lowers fertility among the contributing local skilled, slows human capital accumulation, and reduces the per-capita output growth. The analysis also demonstrates that income redistribution, although financed by taxes levied on the skilled, generates a mechanism that, via its disincentive effect on human capital investment, works strongly against another weak segment of society - the local unskilled. This may provide a purely economic explanation for antipathy toward minorities, especially, among less educated.
Keywords: D3; J1; O0; 330; redistribution; ethnic diversity; fertility; human capital; economic growth; Einkommensverteilung; Ethnische Gruppe; Fertilität; Humankapital; Wirtschaftswachstum; Welt